Determinan Agresivitas Pajak Pada Perusahaan: Kajian Pada Leverage, Likuiditas, Komisaris Independen Dan Manajemen Laba - Agoestina Mappadang (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
The state loses tax revenue, especially from corporate income tax which is quite high every year, this happens because there are still many companies that are doing tax aggressiveness. This study aims to investigate whether corporate tax aggressive have a less transparent information environment. Financial complexity such as leverage and liquidity, independent commissioners, and earnings management affected tax aggressiveness. Effective tax rate (ETR) and cash effective tax rate (CETR) were used to measure tax aggressiveness. The test was conducted for manufacturing firms that were listed on the Indonesian Stock Exchange during the period of 2015-2019. Panel data regression was used to test the hypothesis. The result showed that it failed to find a significant relationship between liquidity and tax aggressiveness. Independent commissioners had a negative impact on tax aggressiveness, but leverage and earning management had a positive impact on tax aggressiveness. Overall, these results important to both financial and tax regulators and other stakeholders, who have a vested interest in understanding the interaction of financial and corporate tax aggressiveness.